KAJIAN LOYALITAS HUBUNGAN KEMITRAAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Kumadji, Srikandi (FIA UB, 2007)
Cooperation to Indonesian nation it represent mechanism to fulfill requirement of economics all its members, appliance improve prosperity of society in that environment, media to develop economics system, and alsoas impeller of its form an social structure which is humanistic and democratic. Therefore, cooperation life in Indonesia society have to be strenghtened and developed in order to reaching prosperous and fair society. This research aim to know and explain factors influence partnership relation loyalty. Pursuant to research result, attainment of member loyalty at cooperation constituted by satisfaction, shall needto be constructed by organizer of cooperation as effort to develop the exertion together as principalityÂ form cooperate meaning that cooperation there are awareness and disabusing of is spirit cooperation and responsibility with the result without thinking of their own interest, but always for bliss together. This matter as anticipatory form because reason of there no alternative besides the cooperation to accomodate result of society production